Consistent Performance Differences between Children and Adults Despite Manipulation of Cue-Target Variables - Bauer, Jessie-Raye; Martinez, Joel E.; Roe, Mary Abbe; Church, Jessica A. (Frontiers in Psychology, 2017)
Two behavioral experiments assessed the plasticity and short-term improvement of task switching in 215 children and adults. Specifically, we studied manipulations of cued attention to different features of a target stimulus as a way to assess the development of cognitive flexibility. Each experiment had multiple levels of difficulty via manipulation of number of cued features (2–4) and number of response options (2 or 4). Working memory demand was manipulated across the two experiments. Impact of memory demand and task level manipulations on task accuracy and response times were measured. There were three overall goals: First, these task manipulations (number of cued features, response choices, and working memory load) were tested to assess the stability of group differences in performance between children ages 6–16 years and adults 18–27 years, with the goal of reducing age group differences. Second, age-related transitions to adult-level performance were examined within subgroups of the child sample. Third, short-term improvement from the beginning to the end of the study session was measured to probe whether children can improve with task experience. Attempts to use task manipulations to reduce age differences in cued task switching performance were unsuccessful: children performed consistently worse and were more susceptible to task manipulations than adults. However, across both studies, adult-like performance was observed around mid-adolescence, by ages 13-16 years. Certain task manipulations, especially increasing number of response options when working memory demand was low, produced differences from adults even in the oldest children. Interestingly, there was similar performance improvement with practice for both child and adult groups. The higher memory demand version of the task (Experiment 2) prompted greater short-term improvement in accuracy and response times than the lower memory demand version (Experiment 1). These results reveal stable differences in cued switching performance over development, but also relative flexibility within a given individual over time.